Quantitative Assessment of the Financial Sector : An Integrated Approach - Worrell, Rupert (IMF Working Papers; Working Paper, 2004)
This paper suggests a strategy designed to make best use of the available quantitative techniques of financial sector assessment. It incorporates early warning systems, financial sector forecasts, stress tests for systemically important financial institutions, interbank contagion analysis, and corporate and household financial indicators. It will seldom be possible to employ every one of these techniques, but the wider the range of methodologies used, the greater may be the insight into the strengths and vulnerabilities of the financial sector. The quantitative assessment is always complemented by a qualitative assessment, including reviews of relevant standards and codes.